Al Capone e i gangster visti dalla Francia: una mafia di cui si mantenne nell’ombra il nome - Volle, Nicolas (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
The appearance in the French press of Al Capone’s banditry compensates the supposed victory of fascism against the Mafia. In the space of a few years, it reveals a new criminality whose operating modes equal those of the Mafia. But this press, dazzled by the violence and novelty of this banditry fails to grasp its similarities to the Mafia. Exposing the ways in which French journalists reveals this criminality, the article questions the reasons why they do not see its proximity to the Mafia.